Understanding teachers' experiences of ventilation in California K‐12 classrooms and implications for supporting safe operation of schools in the wake of the COVID‐19 pandemic. (15th February 2022) - Sanguinetti, Angela; Outcault, Sarah; Pistochini, Theresa; Hoffacker, Madison
Abstract: Classrooms are often under‐ventilated, posing risks for airborne disease transmission as schools have reopened amidst the COVID‐19 pandemic. While technical solutions to ensure adequate air exchange are crucial, this research focuses on teachers' perceptions and practices that may also have important implications for achieving a safe classroom environment. We report on a (pre‐pandemic) survey of 84 teachers across 11 California schools, exploring their perceptions of environmental quality in relation to monitored indoor environmental quality (IEQ) data from their classrooms. Teachers were not educated regarding mechanical ventilation. Errors in HVAC system installation and programming contributed to misunderstandings (because mechanical ventilation was often not performing as it should) and even occasionally made it possible for teachers to turn off the HVAC fan (to reduce noise). Teachers did not accurately perceive (in)sufficient ventilation; in fact, those in classrooms with poorer ventilation were more satisfied with IEQ, likely due to more temperature fluctuations when ventilation rates were higher combined with occupants' tendency to conflate perceptions of air quality and temperature. We conclude that classroom CO2  monitoring and teacher education are vital to ensure that teachers feel safe in the classroom and empowered to protect the health of themselves and their students.